Analysis Z-score to Predict Bankruptcy in Banks Listed in Indonesia Stock Exchange - Khaddafi, Muammar; Falahuddin, Falahuddin; Heikal, Mohd.; Nandari, Ayu (International Journal of Economics and Financial Issues, 2017)
This study aimed to test the predictions of bankruptcy in the banking companies listed in the Indonesia Stock Exchange yy using the Altman Z-score to see how big the bankruptcy prediction period 2011-2013 in the banking company. Calculating each bank's bankruptcy prediction on each numbering 29 banks. The data used in this study is the annual financial statements that are Exchange Indonesia. The analysis technique used is a bankruptcy prediction model Altman Z-score. By using the formula Z-Score = 1,2X1 + 1.4 X2 + 3,3X3 + 0.6 + 1.0 X4 X5. The criteria for assessing a Z-score> 2.99 categorized as a very healthy company. 1.81 <Z-score <2.99 are in the gray area so the chances saved and the possibility of bankruptcy the same amount depends on the discretion of the management company's decision as a decision maker. Z-score <1.81 categorized as a company that has enormous financial difficulties and are at high risk so that the possibility of the collapse of very large. During the period show that the research data of 29 banks that go public are still some who are in a state of bankruptcy. In 2011, there were 13 banks that are in a healthy condition is indicated by the results of the Z-score were above 2.99, and the 14 banks that are in a state of bankruptcy, and two banks that are in Grey area. Whereas in 2012 there were 10 banks in good health, 14 banks were in a state of bankruptcy, and 5 banks in conditions of gray area. In 2013 increased at a healthy bank that there are 11 banks, in conditions of gray area 4 and in a state of bankruptcy remains the same in each year ie 14 banks. Keywords: Altman Z-score, prediction of bankruptcy JEL Classifications: G1, G3,G33